Habilidades matemáticas presentes em alunos do ensino médio participantes em Feiras de Ciências - Giorgion, Rogério (2010)
This piece of work aims to identify mathematical abilities present in middle school students who participate in the Science Fairs. In order to research the relationship between the process of carrying out the work for Science Fairs and the development of mathematical abilities we use the mathematical ability categories made by Krutetskii (1976) and the concepts of the learning theory by Vigotski. Some aspects of the history of the Science Fairs and the teaching of mathematics, including an analysis of curricular changes made in the last few years explain the scenario of the research. The methodology chosen was qualitative and exploratory, since the objective was to identify and analyze what mathematical abilities were present in the subjects of the research: three finalists of the national Fairs with unsatisfactory performance in the regular mathematics course. The tests were inspired in those developed by Krutetskii (1976) and the analysis made confirmed the presence of some of the abilities investigated: perception, spatial perception, mental representation and flexibility